Climate change from a Marxist perspective - walalangi, david; nurfitriana, siti (IULI Publisher, 2024)
Climate change is one of the world's most important challenges today. However, capitalist solutions to climate change dominate the conversation, and Marxist perspectives have been mostly left by the wayside by mainstream ecologists as well as fellow Marxists. This paper aims to utilize recent Marxist works on ecology to analyze various case related to climate change and showcase the flaws in current capitalist understandings of climate change and its potential solutions. Keywords: Climate change, Marxist, capitalist